2022
DOI: 10.3390/antiox11071333
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Lipid Peroxidation-Associated Chemiluminescence in Plants: Spectral Features, Regulation and Origin of the Signal in Leaves and Roots

Abstract: Plants, like most living organisms, spontaneously emit photons of visible light. This ultraweak endogenous chemiluminescence is linked to the oxidative metabolism, with lipid peroxidation constituting a major source of photons in plants. We imaged this signal using a very sensitive cooled CCD camera and analysed its spectral characteristics using bandpass interference filters. In vitro oxidation of lipids induced luminescence throughout the visible spectrum (450–850 nm). However, luminescence in the red spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Green plants have signi cant spectral re ectance properties unlike other features, and the re ectance spectra of plants are closely linked to their growth, development and health 24 . Chlorophyll in plants is most responsive to spectra in the visible light band, absorbing light in both the blue (450 nm) and red (650 nm) wavelength ranges and producing an absorption peak near 550 nm 25 . In this study, the raw spectral re ectance of molehills at different successional stages showed that, except for ZM0, all other molehills showed different degrees of "green peaks" around 550 nm, with ZMM, ZM2, CK, and ZM1 in descending order, which was attributed to the fact that ZM0 had a lower vegetative cover, and therefore showed a spectral type closer to the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Green plants have signi cant spectral re ectance properties unlike other features, and the re ectance spectra of plants are closely linked to their growth, development and health 24 . Chlorophyll in plants is most responsive to spectra in the visible light band, absorbing light in both the blue (450 nm) and red (650 nm) wavelength ranges and producing an absorption peak near 550 nm 25 . In this study, the raw spectral re ectance of molehills at different successional stages showed that, except for ZM0, all other molehills showed different degrees of "green peaks" around 550 nm, with ZMM, ZM2, CK, and ZM1 in descending order, which was attributed to the fact that ZM0 had a lower vegetative cover, and therefore showed a spectral type closer to the soil.…”
Section: Discussionmentioning
confidence: 99%
“…101 LP causes oxidative degradation of lipids in the cell membrane, leads to the oxidation of protein SH groups, and inhibits the synthesis of proteins and enzymes, which provokes cell death. 102 During the LP process, primary and secondary metabolites are formed such as conjugated dienes (CDs) and malonic dialdehyde (MDA), respectively. 103 LP products are toxic compounds that alter the functional properties of biopolymers.…”
Section: Effect Of Manganese Nanoparticles On Plantsmentioning
confidence: 99%
“…The interaction of PUFAs with ROS triggers successive LP reactions . LP causes oxidative degradation of lipids in the cell membrane, leads to the oxidation of protein SH groups, and inhibits the synthesis of proteins and enzymes, which provokes cell death . During the LP process, primary and secondary metabolites are formed such as conjugated dienes (CDs) and malonic dialdehyde (MDA), respectively .…”
Section: Effect Of Manganese Nanoparticles On Plantsmentioning
confidence: 99%
“…The work of V.Y. Horgan et al [4,5,6] revealed the high toxicity of lipid peroxides accumulating in the irradiated organism. Low-molecular toxic substances were found in the blood of irradiated animals and plants [7,8].…”
Section: Introductionmentioning
confidence: 99%